Trials of engagement : the future of US public diplomacy - Fisher, Ali; Lucas, Scott (Diplomatic studies ;, 2011)
In the last decade public diplomacy has become one of the most important concepts in the development and implementation of foreign policy. Trials of Engagement: The Future of US Public Diplomacy, with contributors from leading scholars in disciplines from international relations to communications, considers the challenges for this 'new' public diplomacy, especially as it is pursued by the US Government. It highlights the challenges of aligning policy and projection, overcoming bureaucratic tensions, and the language used by public diplomats. Most importantly, the volume illustrates that the is.